New sulfuryl fluoride-derived alkylating reagents for the 1, 1-dihydrofluoroalkylation of thiols. Issue 44 (27th September 2019) - Foth, Paul J.; Gu, Frances; Bolduc, Trevor G.; Kanani, Sahil S.; Sammis, Glenn M.
Abstract : Herein, we report a new method for the one-pot synthesis of 1, 1-dihydrofluoroalkyl sulfides by bubbling sulfuryl fluoride (SO2 F2 ) through a solution of the corresponding alcohol and thiol. Abstract : Herein, we report a new method for the one-pot synthesis of 1, 1-dihydrofluoroalkyl sulfides by bubbling sulfuryl fluoride (SO2 F2 ) through a solution of the corresponding alcohol and thiol. The reaction proceeds through a new class of bis(1, 1-dihydrofluoroalkyl) sulfate reagents, to afford the desired 1, 1-dihydrofluoroalkyl sulfides in 55–90% isolated yields. The bis(1, 1-dihydrofluoroalkyl) sulfates are highly chemoselective for thiol alkylation, and are unreactive with competing, unprotected nucleophiles, including amines, alcohols, and carboxylic acids.